Standard translation twists and an operator-bounded energy inequality - Casini, Horacio German (2024)
Twist operators implement symmetries in bounder regions of the space. Standard twists are a special class of twists constructed using modular tools. The twistscorresponding to translations have interesting special properties. They can move continuously an operator from a region to a disjoint one without ever passing throughthe gap separating the two. In addition, they have generators satisfying the spectrumcondition. We compute explicitly these twists for the two dimensional chiral fermionfield. The twist generator gives place to a new type of energy inequality where thesmeared energy density is bounded below by an operator.